Perbandingan Penggunaan Straight Line Method Dan Double Declining Balance Method Pada Aset PT. Delimas Lestari Jaya - Dina Satriani; Asep Saifudin; Po Abas Sunarya (CICES (Cyberpreneurship Innovative and Creative Exact and Social Science), 2020)
PT. Delimas Lestari Jaya As one of the companies engaged in general trading and services of construction and Real Estate category. Assets remain instrumental in the operational activities of a company. Therefore, there needs to be appropriate management of fixed assets to be utilized according to the needs of the company. Generate different depreciation loads. Depreciation of fixed assets is calculated since the operation month or the month of fixed asset acquisition. Likewise if using depreciation. The purpose of this research is to know the depreciation of fixed assets according to PSAK No. 16, to determine the value of depreciation of fixed assets when using other depreciation methods, and to determine the company's management policy on the fixed asset treatment it has, and to compare depreciation load result between A straight line method and a declining balance method.